Diverting 911 calls: Lessons from early adopting urban jurisdictions - Midgette, Greg (Criminology & public policy, 2024)
Research Summary Two perceptions drive interest in finding ways of diverting more 911 calls from police to civilian first responders: (1) police responses can result in inadvertent harm to citizens and (2) many calls to which police respond require services that police often cannot provide. Thus, using other personnel may improve police-citizen relations and strengthen crime fighting by reducing extraneous police burden. Using a case study design, we conducted formative evaluations of programs that have developed beyond pilots in three large U.S. cities: Albuquerque, Atlanta, and Houston. In each city, we interviewed officials, program operators, and other stakeholders and reviewed program documents and statistics. We detail the events and forces that led to the establishment of each program, the way in which the programs have been institutionalized, and the way they interact with the police department. We then discuss key lessons learned for these jurisdictions. Policy Implications Many U.S. cities are considering diverting some emergency calls for service from police to civilian first responders. This analysis provides evidence to aid policy makers, researchers, and other stakeholders in the development and evaluation of community responder programs. In all respects, we find that cities’ unique experiences inform program design. For example, in Albuquerque, a City Hall-driven initiative established a new city agency parallel to the police department. In Atlanta, decarceration activists drove the initiative; the program is a city/county-funded nonprofit, more fragile in its funding. Risk aversion among call takers and dispatchers has led to low call diversion rates across all sites, but training and collaboration have shown promise to resolve this problem. Public safety officials external to the diversion programs commonly expressed concerns about first responder safety and perceptions that police are expected when 911 is called. This risk aversion has led to slower-than-expected expansion of the program within each city.